Fabricating and Testing of Porous Magnesium Through Powder Metallurgy Technique using TWSH (Titanium Wire Space Holder) for Biodegradable Bone Scaffold Material - Irza Sukmana; S Savetlana; Y Burhanudin; M A Wicaksono; Hadi Nur (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2019)
Magnesium (Mg) and its alloys seem to be a potential biodegradable bone scaffold materials as their biocompatibility and mechanical properties fit to natural bone. Magnesium alloys as biomaterials have higher mechanical properties that may close to cancellous bone once composed and produced in a specific production route. Fabricating porous magnesium for bone scaffold material aims to reduce the rigidity and strength of the material by which the porous density can be adjusted to the original nature of the bone. It forms interconnected porosity, has physical and mechanical properties similar to cancellous bone. This paper describes the production and characterization of porous magnesium material for the potential application as bone scaffold through powder metallurgy technique with pieces of Titanium Wire Space Holder. Mg containing titanium pieces were then compacted and sintered before immersed in hydro fluoride acid solution to form a porous magnesium structure. Density and porosity, micro Vickers hardness, micro structure test and SEM-EDX were performed to prove the existing porous structure inside Mg metal. The result finds out that a good cooperation and a potential application for the fabrication of an inter-connected porous magnesium samples for cancellous bone implant.